Klasifikasi Status Idle dan Kerja Wheel Loader WA350 Berbasis Akselerometer Tunggal - Dhendy Zaki Ridwan; Branjangan, Panji Peksi; Winarko, Wigo Ardi (Politeknik Negeri Malang, 2025)
Conventional hour meters on heavy equipment accumulate engine-ON time without distinguishing productive working from non-productive idle, which can bias preventive maintenance scheduling. This study evaluates the feasibility of separating idle and working conditions of a Komatsu WA350 wheel loader using a single tri-axial accelerometer. Vibration data were recorded at 700, 900, 1100, and 1300 rpm under two scenarios: engine-on with bucket stationary (idle) and engine-on with bucket actuation without load (working). The main indicator is the time-domain Root Mean Square (RMS) on AccX, AccY, and AccZ to represent vibration energy per axis, supported by low-frequency spectral inspection for interpretation. For paired comparison, the analysis focuses on 700–1100 rpm because the 1300 rpm dataset does not include a verified idle counterpart. The results show that AccX provides the most consistent separation, where RMS in working increases by approximately 10–13% compared to idle at 700–1100 rpm, while AccY is less stable and AccZ changes are minimal. These findings support a simple RMS-based logic as a practical basis for smart hour-metering to better reflect operational workload and improve service notification timing. Limitations include controlled test conditions (no-load bucket cycles) and a single mounting location; broader validation under varied loads, terrains, and operators is required.